Mental Health as Intervening Variable on Relationship of Social Support and Achievement of Qur'an Memorization - Ridwan, Ari Mohamad; Fauzan, Muhammad (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The 2022 Indonesian National Youth Mental Health Survey informed that adolescents were diagnosed around 1 in 20 or 5.5 percent of with condition of mental disorders. Basically, social support can encourage adolescents to have good mental health, so they can achieve their dreams. Especially for adolescents in memorizing the Qur'an. This study was to analyze the effect of social support on the achievement of memorizing the Qur'an and mental health as an intervening variable. The research method used quantitative with a survey approach. Based on the data obtained, there is a relationship between social support and the achievement of memorizing the Qur'an through mental health. The results of the study showed that social support was significantly related to mental health. It is known that out of 94 people, there are 60 people (63.8%) in the moderate category, which proves that the relationship between social support and mental health and is strengthened by the Sommers'd test which shows that the correlation is quite strong with a p value of 0.007 <0.05 which means that there is a relationship between social support and mental health on the achievement of memorizing the Qur'an. The novelty of this study lies in its concept, namely that social support can affect the achievement of memorizing the Qur'an through mental health because good social support will produce a healthy mentality, and a healthy mentality will make the memorizer of the Qur'an enjoy the process of memorizing it.